Pemberdayaan Perempuan Melalui Microfinance :Suatu Telaah Kebijakan Penanggulangan Kemiskinan - Aryo, Bagus (UI Scholars Hub, 2006)
Woman is an adequate partner to microfinance because not only assisting women but also their families and society. There’re some challenges and constraints faced by women related to microenterprises such as norm, cultural, mobility, lameness gender, work without “payment